Carbon dioxide solid adsorption gel as well as preparation method and application thereof
By combining acid-soluble chitosan with desulfurization wastewater, sodium alginate and TRIS and other components to prepare carbon dioxide solid adsorption gel, the problems of high cost and insufficient adsorption capacity of existing adsorbents are solved, and efficient carbon dioxide capture and low carbon dioxide Analytical temperature, suitable for the recycling of carbon dioxide.
Patent Information
- Application Number
- CN202411635440.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing carbon dioxide adsorbents are expensive and have limited adsorption capacity to carbon dioxide, making carbon dioxide difficult to resolve, which is not conducive to the recycling and utilization of carbon dioxide.
The carbon dioxide solid adsorption gel is prepared by combining acid-soluble chitosan with natural products such as desulfurization wastewater, sodium alginate and TRIS through stirring, heating, freezing and drying, and the acidic and hydrogen ions in the desulfurization wastewater are used to promote cross-linking. Form a high-strength hydrogel that captures carbon dioxide.
It reduces the manufacturing cost of adsorbents, improves the capture effect of carbon dioxide, and has a low analytical temperature after capture, which is suitable for the capture and utilization of carbon dioxide.
Smart Images

Figure BDA0005137037890000071 
Figure BDA0005137037890000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide capture, and in particular to a carbon dioxide solid adsorption gel and a preparation method and application thereof. Background Art
[0002] Carbon capture aims to collect and purify carbon dioxide from industrial production, energy activities or the atmosphere, and then directly utilize or store it to achieve the purpose of reducing carbon emissions. Carbon capture technology includes chemical absorption, physical absorption, adsorption separation and other methods; among them, chemical absorption mainly uses the chemical reaction between chemical reagents and carbon dioxide to capture carbon dioxide, and physical absorption mainly uses the property that the solubility of certain physical solvents in carbon dioxide is much greater than that of other components to achieve the separation of carbon dioxide.
[0003] Adsorption separation mainly uses the difference in attraction between the active points on the adsorbent surface and different gas molecules to separate different gas components. At present, adsorbents used for carbon dioxide adsorption separation are generally porous materials, and commonly used adsorbents include molecular sieves, activated carbon, silica gel, activated alumina, etc. However, most adsorbents are relatively expensive and have limited adsorption capacity for carbon dioxide. In addition, carbon dioxide analysis is difficult, which is not conducive to the recycling of carbon dioxide.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a carbon dioxide solid adsorption gel and a preparation method and application thereof. The carbon dioxide solid adsorption gel has high strength and excellent carbon dioxide capture effect.
[0006] The present invention provides a method for preparing a carbon dioxide solid adsorption gel, comprising the following steps:
[0007] S1: fully stirring and mixing the acid-soluble chitosan and the desulfurization wastewater to prepare a chitosan solution;
[0008] S2: The chitosan solution and the sodium alginate solution are fully stirred and mixed and then heated to obtain a viscous solution;
[0009] S3: Add lime milk to the desulfurization wastewater to neutralize it to neutrality, then add TRIS, stir and dissolve it thoroughly to obtain a mixed solution;
[0010] S4: adding the viscous liquid dropwise into the mixed liquid to form a hydrogel, taking out the hydrogel, freezing and drying it, and obtaining a carbon dioxide solid adsorption gel.
[0011] In the present invention, the pH value of the desulfurization wastewater is 5-6; the mass content of calcium chloride in the desulfurization wastewater is 12-15 mg / L, and the mass content of magnesium chloride is 10-12 mg / L.
[0012] In step S1, the mass ratio of acid-soluble chitosan to desulfurization wastewater is 1:(5-8). Using desulfurization wastewater to dissolve acid-soluble chitosan can not only utilize the acidity of desulfurization wastewater to dissolve acid-soluble chitosan well, but also protonate the amino groups of acid-soluble chitosan without affecting its carbon dioxide absorption function, and in particular, can simultaneously realize the resource utilization of desulfurization wastewater.
[0013] In step S2, the mass content of the sodium alginate solution is 2-4%; the mass ratio of the viscous substance to the sodium alginate solution is 1:(1-2); the heating temperature is 50-70°C, and the heating time is 2-4 hours. The chitosan solution and the sodium alginate solution are fully stirred and mixed, and the hydrogen ions in the desulfurization wastewater are used to promote the carboxyl group of the alginate and the amino group of the chitosan to form an ester group, so that the cross-linking is more firm.
[0014] In step S3, the mass content of TRIS in the mixed solution is controlled to be 10-15%. The chloride ion component in the desulfurization wastewater can make TRIS present a liquid-solid intermediate state, which will not be precipitated, so that the hydroxide ions can be fully utilized; the lime milk (i.e. calcium hydroxide) is a sodium alginate-chitosan crosslinker, which enhances the strength of the hydrogel. At the same time, after the calcium ions are captured, more hydroxide and TIRs are coated by the gel, and the metal ions are captured. The decomposition temperature of the gel is greatly degraded, and the decomposition temperature of the gel after capture is 60-80°C.
[0015] In step S4, the freezing temperature is -18°C to -22°C, the freezing time is 6-10 hours, and the drying is vacuum drying, the drying time is 20-30 hours. Through freezing and drying, a gel with sufficient strength can be obtained, which contains chitosan amino groups and molten TRIS, and is coated with a large amount of hydroxide, and has an excellent effect of directly capturing carbon dioxide in the air.
[0016] The present invention also provides a carbon dioxide solid adsorption gel, which is prepared according to the above preparation method.
[0017] The present invention also provides application of the carbon dioxide solid adsorption gel in carbon dioxide adsorption.
[0018] The present invention relies on natural products such as chitosan and combines with desulfurization wastewater treatment to prepare carbon dioxide solid adsorption gel, which not only greatly reduces the manufacturing cost of the adsorbent, but also can effectively treat desulfurization wastewater. The prepared carbon dioxide solid adsorption gel not only has an excellent carbon dioxide capture effect, but also has a low decomposition temperature after capture, which is particularly beneficial to the capture and utilization of carbon dioxide. DETAILED DESCRIPTION
[0019] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0020] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] In this embodiment, desulfurization wastewater is used to prepare carbon dioxide solid adsorption gel, the pH value of the desulfurization wastewater is 5.5, the mass content of calcium chloride is 12 mg / L, and the mass content of magnesium chloride is 10 mg / L. The preparation method steps are as follows:
[0024] 1) Preparation of chitosan solution
[0025] The acid-soluble chitosan and the supernatant of desulfurization wastewater were fully stirred and mixed at a mass ratio of 4:25 to prepare a chitosan solution.
[0026] 2) Preparation of viscous liquid
[0027] The chitosan solution and the sodium alginate solution with a mass content of 3% were fully stirred and mixed in a mass ratio of 1:1, and then heated at 60° C. for 3 h to obtain a viscous solution.
[0028] 3) Preparation of mixed solution
[0029] Lime milk is added to the desulfurization wastewater to neutralize it to neutrality, and then TRIS is added and fully stirred to dissolve to obtain a mixed solution; wherein the mass content of TRIS in the mixed solution is 12%.
[0030] 4) Freezing and drying
[0031] The viscous liquid of step 2) is added dropwise to the mixed liquid of step 3) by gravity through a syringe to form a hydrogel; the hydrogel is taken out, first frozen at -18°C for 8 hours, and then vacuum dried for 24 hours to obtain a carbon dioxide solid adsorption gel.
[0032] Example 2
[0033] In this embodiment, desulfurization wastewater is used to prepare carbon dioxide solid adsorption gel, the pH value of the desulfurization wastewater is 5.5, the mass content of calcium chloride is 13 mg / L, and the mass content of magnesium chloride is 11 mg / L. The preparation method steps are as follows:
[0034] 1) Preparation of chitosan solution
[0035] The acid-soluble chitosan and the supernatant of desulfurization wastewater were fully stirred and mixed at a mass ratio of 1:5 to prepare a chitosan solution.
[0036] 2) Preparation of viscous liquid
[0037] The chitosan solution and the sodium alginate solution with a mass content of 2% were fully stirred and mixed in a mass ratio of 1:1, and then heated at 50° C. for 4 hours to obtain a viscous liquid.
[0038] 3) Preparation of mixed solution
[0039] Lime milk is added to the desulfurization wastewater to neutralize it to neutrality, and then TRIS is added and fully stirred to dissolve to obtain a mixed solution; wherein the mass content of TRIS in the mixed solution is 10%.
[0040] 4) Freezing and drying
[0041] The viscous liquid of step 2) is added dropwise to the mixed liquid of step 3) by gravity through a syringe to form a hydrogel; the hydrogel is taken out, first frozen at -20°C for 10 hours, and then vacuum dried for 20 hours to obtain a carbon dioxide solid adsorption gel.
[0042] Example 3
[0043] In this embodiment, desulfurization wastewater is used to prepare carbon dioxide solid adsorption gel. The pH value of the desulfurization wastewater is 6, the mass content of calcium chloride is 13 mg / L, and the mass content of magnesium chloride is 11 mg / L. The preparation method steps are as follows:
[0044] 1) Preparation of chitosan solution
[0045] The acid-soluble chitosan and the desulfurization wastewater supernatant were fully stirred and mixed at a mass ratio of 1:8 to prepare a chitosan solution.
[0046] 2) Preparation of viscous liquid
[0047] The chitosan solution and the sodium alginate solution with a mass content of 2% were fully stirred and mixed in a mass ratio of 1:2, and then heated at 70° C. for 2 h to obtain a viscous solution.
[0048] 3) Preparation of mixed solution
[0049] Lime milk is added to the desulfurization wastewater to neutralize it to neutrality, and then TRIS is added and fully stirred to dissolve to obtain a mixed solution; wherein the mass content of TRIS in the mixed solution is 15%.
[0050] 4) Freezing and drying
[0051] The viscous liquid of step 2) is added dropwise to the mixed liquid of step 3) by gravity through a syringe to form a hydrogel; the hydrogel is taken out, first frozen at -22°C for 6 hours, and then vacuum dried for 30 hours to obtain a carbon dioxide solid adsorption gel.
[0052] Comparative Example 1
[0053] The preparation method of the carbon dioxide solid adsorption gel of this comparative example is as follows:
[0054] 1) Preparation of chitosan solution
[0055] The acid-soluble chitosan and the ester acid solution with a pH value of 5.5 were fully stirred and mixed in a mass ratio of 4:25 to prepare a chitosan solution.
[0056] 2) Preparation of viscous liquid
[0057] The chitosan solution and the sodium alginate solution with a mass content of 3% were fully stirred and mixed in a mass ratio of 1:1, and then heated at 60° C. for 3 h to obtain a viscous solution.
[0058] 3) Preparation of mixed solution
[0059] An equal amount of lime milk to that in Example 1 was added to water, and then TRIS was added, and the mixture was stirred thoroughly to dissolve, thereby obtaining a mixed solution; wherein the mass content of TRIS in the mixed solution was 12%.
[0060] 4) Freezing and drying
[0061] The viscous liquid of step 2) is added dropwise to the mixed liquid of step 3) by gravity through a syringe to form a hydrogel; the hydrogel is taken out, first frozen at -18°C for 8 hours, and then vacuum dried for 24 hours to obtain a carbon dioxide solid adsorption gel.
[0062] Comparative Example 2
[0063] The process is the same as that of Example 1 except that 0.01 mol / L sodium hydroxide solution is used to replace the lime milk in step 3) of Example 1.
[0064] Comparative Example 3
[0065] Except that TRIS is not added in step 3) when preparing the mixed solution, the rest is the same as Example 1.
[0066] Comparative Example 4
[0067] Except for using pure water instead of desulfurization wastewater, the rest is the same as Example 1.
[0068] Test Example 1
[0069] The carbon dioxide solid adsorption gel prepared in Example 1 was used to carry out a gas adsorption test; the gas adsorption test method is as follows:
[0070] The test was conducted in a 30 cubic sealed laboratory equipped with a carbon dioxide sensor and a fan. The carbon dioxide solid adsorption gel was filled into the fan inlet and fixed with non-woven fabric to form a 2 cm thick adsorption layer. The initial concentration of carbon dioxide in the laboratory before the adsorption test was 500 ppm. 3 The carbon dioxide concentration after adsorption for different time at air volume / h is shown in Table 1.
[0071] Table 1 Carbon dioxide concentration after adsorption for different time
[0072] Adsorption time (min) Carbon dioxide concentration (ppm) 0 500 1 462 2 418 3 378 4 346 5 319 6 287 7 253 8 215 9 181 10 144
[0073] Test Example 2
[0074] The carbon dioxide solid adsorption gel prepared in each embodiment and the control example was used to carry out a gas adsorption test. The test method was the same as that in Test Example 1. Each carbon dioxide solid adsorption gel was heated at 300 m 3 The carbon dioxide concentration after adsorption for 10 minutes at an air volume of / h is shown in Table 2.
[0075] Table 2 Adsorption results of different carbon dioxide solid adsorption gels
[0076]
[0077]
[0078] Test Example 3
[0079] The carbon dioxide solid adsorption gel in Test Example 2 was analyzed after adsorption for 10 minutes. The analysis temperature was 60°C and the analysis time was 12 hours. The carbon dioxide solid adsorption gel prepared in each embodiment and control example was subjected to gas adsorption test. The test method was the same as that in Test Example 1. Each carbon dioxide solid adsorption gel was heated at 300m 3 The carbon dioxide concentration after adsorption for 10 minutes at an air volume of / h is shown in Table 3.
[0080] Table 3 Adsorption results of different carbon dioxide solid adsorption gels
[0081] Carbon dioxide solid adsorption gel Carbon dioxide concentration (ppm) Example 1 145 Example 2 158 Example 3 123 Comparative Example 1 257 Comparative Example 2 333 Comparative Example 3 292 Comparative Example 4 256
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a carbon dioxide solid adsorption gel, characterized in that: The steps include: S1: fully stirring and mixing the acid-soluble chitosan and the desulfurization wastewater to prepare a chitosan solution; S2: The chitosan solution and the sodium alginate solution are fully stirred and mixed and then heated to obtain a viscous solution; S3: Add lime milk to the desulfurization wastewater to neutralize it to neutrality, then add TRIS, stir and dissolve it thoroughly to obtain a mixed solution; S4: adding the viscous liquid dropwise into the mixed liquid to form a hydrogel, taking out the hydrogel, freezing and drying it, and obtaining a carbon dioxide solid adsorption gel.
2. The preparation method according to claim 1, characterized in that: The pH value of desulfurization wastewater is 5-6; the mass content of calcium chloride in desulfurization wastewater is 12-15 mg / L, and the mass content of magnesium chloride is 10-12 mg / L.
3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of acid-soluble chitosan to desulfurization wastewater is 1:(5-8).
4. The preparation method according to claim 1, characterized in that: In step S2, the mass content of the sodium alginate solution is 2-4%; the mass ratio of the viscous substance to the sodium alginate solution is 1:(1-2).
5. The preparation method according to claim 1, characterized in that: In step S2, the heating temperature is 50-70°C and the heating time is 2-4h.
6. The preparation method according to claim 1, characterized in that: In step S3, the mass content of TRIS in the mixed solution is controlled to be 10-15%.
7. The preparation method according to claim 1, characterized in that: In step S4, the freezing temperature is -18°C to -22°C, and the freezing time is 6-10 hours.
8. The preparation method according to claim 1, characterized in that: In step S4, vacuum drying is used for drying, and the drying time is 20-30 hours.
9. A carbon dioxide solid adsorption gel, characterized in that: Prepared according to any one of the preparation methods of claims 1-8.
10. Use of the carbon dioxide solid adsorption gel according to claim 9 in carbon dioxide adsorption.
Citation Information
Patent Citations
Modular reactor and process for carbon dioxide extraction
CN102170955A
Hydrogels and methods of making same
CN107522880A
Microfluidic technology for one-step continuous preparation of calcium alginate microgel
CN107930542A
Chitosan / alginic acid and anthocyanin interface synergistic effect stable Pickering emulsion
CN115715761A
Aminated chitosan / sodium alginate composite porous gel microspheres as well as preparation method and application thereof
CN117942950A